(untitled) (Itinera, 2024)
This paper examines some essential dichotomies in Carlo Collodi’s Le avventure di Pi- nocchio. Storia di un burattino through its implications on the level of comic and popular culture. On the one hand, starting from chapters I-III and VIII, it analyses Collodi’s reflec- tion on artistic creation and its connection with fatherhood, especially on its binarisms («artista»/«pezzo di legno», «idea»/«burattino», reality/imagination, and so on). On the other hand, it delves into the relation between the “body” and the “order”, as well as the close connection with the issue of “transgression”, that in Pinocchio is validated both in ethic and aesthetic terms.